2014
DOI: 10.1007/s00455-014-9531-z
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Passive Motion of Para- and Retropharyngeal Structures During Swallowing Using Dynamic Magnetic Resonance Imaging

Abstract: The purpose of this study was to analyze passive motion of the para- and retropharyngeal space (PRS) during swallowing using dynamic magnetic resonance imaging (MRI). We conducted a preliminary study involving 30 healthy volunteers who underwent dynamic MRI. Consecutive MRI axial images were obtained by examining the plane parallel to the hard palate at the level of the anterior inferior corner of C2. Anterior displacement of the posterior pharyngeal wall (PPW) was measured as a motion index of pharyngeal cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
17
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(21 citation statements)
references
References 21 publications
2
17
0
Order By: Relevance
“…A recent study of the motion of parapharyngeal and retropharyngeal structures during swallowing has shown that there is anterior and medial displacement of the ICA and external carotid artery during pharyngeal contraction. 13 In our study, the variability in the position of the retropharyngeal carotid arteries was at the level of the hyoid bone in all patients (Figs 2 and 3). The ICA may potentially be temporarily held in a retropharyngeal position by the tip of the greater cornu of the hyoid bone after being drawn anteromedially by pharyngeal contraction during swallowing, though this theory cannot be confirmed by our study, and the duration of the carotid artery being located in any given position cannot be known in our patient population.…”
Section: Discussionmentioning
confidence: 98%
“…A recent study of the motion of parapharyngeal and retropharyngeal structures during swallowing has shown that there is anterior and medial displacement of the ICA and external carotid artery during pharyngeal contraction. 13 In our study, the variability in the position of the retropharyngeal carotid arteries was at the level of the hyoid bone in all patients (Figs 2 and 3). The ICA may potentially be temporarily held in a retropharyngeal position by the tip of the greater cornu of the hyoid bone after being drawn anteromedially by pharyngeal contraction during swallowing, though this theory cannot be confirmed by our study, and the duration of the carotid artery being located in any given position cannot be known in our patient population.…”
Section: Discussionmentioning
confidence: 98%
“…These events can be explained by the anatomic characteristics that RPS locates immediately posterior to the mucosa of the pharynx. In 1 study, the incidence of RCA has been reported to be 15.5% in cancer patients [1] . Four out of 63 patients (6.3%) had been confirmed to have a unidirectional change in the carotid arteries from the RPS to the lateral or vice versa [1] .…”
Section: Discussionmentioning
confidence: 98%
“…Variations in the anatomic position including that of the retropharyngeal carotid artery (RCA) are relatively rare [1] , [2] . These anatomic variations can cause fatal complications during biopsy or surgery in the head and neck region including the pharynx.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Tumor fixation to the carotid artery can be assessed by passive and spontaneous motions. In our previous study, we found that morphological changes tend to occur around the pharynx during pharyngeal swallowing, when constrictor muscle‐squeezing mechanisms cause parapharyngeal structures to migrate in the direction of the pharyngeal airspace (see Figure ). Recently, clear motions of anatomic details in the head and neck region were visualized using dynamic MRI .…”
Section: Introductionmentioning
confidence: 99%